Mesenchymal Stem Cell-Derived Extracellular Vesicles: A Potential Therapy for Diabetes Mellitus and Diabetic Complications - Fengtian Sun; Yuntong Sun; Feng Wu; Wenrong Xu; Hui Qian (MDPI AG, 2022)
As a novel cell-free strategy, mesenchymal stem cell-derived extracellular vesicles (MSC-EVs) inherit the therapeutic potential of donor cells, and are widely used for the treatment of many diseases. Increasing studies have shown that MSC-EVs transfer various bioactive molecules to create a beneficial microenvironment, thus exerting protective roles in diabetic mellitus (DM) and diabetic complications. To overcome the limitations of natural MSC-EVs such as heterogeneity and insufficient function, several modification methods have been established for constructing engineered MSC-EVs with elevated repairing efficiency. In this review, the PubMed library was searched from inception to August 2022, using a combination of Medical Subject Headings (MeSH) and keywords related to MSC-EVs, DM, and diabetic complications. We provide an overview of the major characteristics of MSC-EVs and summarize the recent advances of MSC-EV-based therapy for hyperglycemia-induced tissue damage with an emphasis on MSC-EV-mediated delivery of functional components. Moreover, the potential applications of engineered MSC-EVs in DM-related diseases therapy are discussed by presenting examples, and the opportunities and challenges for the clinical translation of MSC-EVs, especially engineered MSC-EVs, are evaluated.